2010
DOI: 10.1007/s13277-010-0104-y
|View full text |Cite
|
Sign up to set email alerts
|

CD117, Ki-67, and p53 predict survival in neuroendocrine carcinomas, but not within the subgroup of small cell lung carcinoma

Abstract: High-grade neuroendocrine carcinomas (NECs) are aggressive tumors with limited treatment options. Recently, studies have observed that the tyrosine kinase receptor CD117 is often overexpressed in this malignancy. As a result, CD117 has been identified as a target for therapy via the small molecule, tyrosine kinase inhibitor imatinib mesylate. In the present study, 17 low-grade, 4 intermediate-grade, and 76 high-grade NECs were immunostained for CD117, Ki-67, and p53. Overexpression of the three markers was mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 15 publications
1
14
2
Order By: Relevance
“…In fact, our patient showed an exceptionally low Ki-67 labeling index (3.7%). In addition, several studies on neuroendocrine tumors have reported that bcl-2 or p53 expression might be correlated with malignant behavior [1317, 19, 2327]. However, no studies were found in which investigation was limited to SPC.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our patient showed an exceptionally low Ki-67 labeling index (3.7%). In addition, several studies on neuroendocrine tumors have reported that bcl-2 or p53 expression might be correlated with malignant behavior [1317, 19, 2327]. However, no studies were found in which investigation was limited to SPC.…”
Section: Discussionmentioning
confidence: 99%
“…However, this hypothesis is outside the scope of the present study. Other molecules which may further subdivide lung cancers include Ki67 (6), p53 (7), carcinoembryonic antigen (8), vascular endothelial growth factor (911), epithelial membrane antigen (11) and cytokeratin 5/6 (12), all of which have been suggested to influence disease progression and patient survival. A major problem for individualizing therapy is understanding the tumor characteristics of individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…It supports mitotic count to discriminate between low grade versus high grade tumours and also helps to distinguish these cases by immunohistochemical staining of cytological smears (16,17). It may reflect the tumour grade and predicts survival (18).…”
Section: Clinico-pathological Parametersmentioning
confidence: 69%